Application of Aeromagnetic Data to Assess the Structures, Mineralisation-Porphyry Systems and 2D Modelling of Parts of Northwest Nigeria - Akpaneno, A. F.; Abdullahi, H. A. (European Journal of Applied Sciences, 2026)
This study takes a close look at high-resolution aeromagnetic data to map out structures, porphyry-style mineralization systems, and the basement configuration in parts of northwestern Nigeria, specifically the Maru, Anka, and Zuru schist belts, along with the nearby Sokoto Basin. The total magnetic intensity data was processed through upward continuation and reduced to the pole, then enhanced using various techniques like analytic signal, first vertical derivative, the application of 3D Euler deconvolution and the Centre for Exploration Targeting (CET) structural and porphyry plug-ins. We constructed three 2D magnetic models along profiles across the basin margin using GM-SYS to better understand the basement relief beneath the sedimentary cover. The analytic signal and first vertical derivative maps effectively distinguish a weakly magnetic sedimentary area in the west from a strongly magnetic basement terrain in the east, revealing major lineaments that primarily trend WNW-ENE, NE-SW, NNE-SSW, and NW-SE. The CET structural density mapping points out zones with high and very high structural densities, while the CET porphyry analysis identifies circular to subcircular magnetic centres that align with these structurally complex areas. Euler solutions suggest that most depth ranges in the basement sector are shallower than 450 m, with some deeper solutions found beneath the sedimentary basin. The 2D models indicate sediment thickness ranging from about 0.55 to 1.2 km over a gently undulating crystalline basement. The combined results highlight several structurally prepared, alteration-related targets that show promise for gold and Pb-Zn mineralization in both the schist belt basement and the Sokoto Basin margin.